Visual prosody in Korean Sign Language: (non)manual cues for boundary and prominence - Lee, Jungah; Choi, Youngju (Frontiers in Psychology, 2025)
IntroductionThis study examines how manual and nonmanual features contribute to prosodic marking in Korean Sign Language (KSL), particularly for prominence and Accentual Phrase (AP) boundaries. While previous studies have emphasized the role of nonmanuals in marking prosodic boundaries, we investigate whether these cues in KSL primarily serve to indicate prominence, regardless of boundary position.MethodsSix adult Deaf KSL signers participated in a controlled card-arrangement task designed to elicit target signs in four prosodic conditions: focused vs. unfocused prominence and AP-initial vs. AP-medial positions. The resulting data were analyzed using Bayesian mixed-effects modeling, with two predictors: prominence (focused vs. unfocused) and boundary position (AP-initial vs. AP-medial). A range of manual and nonmanual features—including eye contact, eyebrow movements, and sign duration—were annotated and statistically evaluated to determine their association with prosodic prominence and boundary marking in KSL.ResultsThe results showed that prominence had a robust effect on both manual and nonmanual cues. Features like eye contact, furrowed eyebrows, and squinted eyes were significantly more frequent in focused conditions. In contrast, boundary position alone showed minimal impact, with few features differing between AP-initial and AP-medial positions. Although some interaction effects were found, they were not consistent across features.DiscussionThese findings suggest that KSL prosody is prominence-driven, with nonmanuals functioning as primary markers of focus rather than of AP boundaries. By highlighting the prominence-driven nature of prosodic marking in KSL, this study contributes to a growing body of cross-linguistic research showing that prosodic strategies in sign languages are not uniform but shaped by language-specific implementations.